Case Report: Rapid cataract development preceding diabetes mellitus in WFS1 spectrum disorder - Gulani, Aaishwariya A.; Duggan, Courtney; Ledoux, Danielle M.; Gaier, Eric D. (Frontiers in Ophthalmology, 2025)
WFS1 spectrum disorder is a rare condition, characterized by diabetes insipidus, diabetes mellitus, optic atrophy, and deafness (DIDMOAD). A 2-year-old female patient with a history of sensorineural hearing loss presented with rapid, sequential cataract development. Diabetes mellitus was not manifested at the time but developed 4 years later. While cataracts have been described in this syndrome, rapid acquisition of cataracts in the setting of mild hyperglycemia was unique considering they could not be definitively attributed to diabetes mellitus alone. This case provides real-world evidence that rapid WFS1-related cataract development may result from the underlying condition in conjunction with or independent from WFS1-associated diabetes mellitus.